2014
DOI: 10.1002/chem.201304284
|View full text |Cite
|
Sign up to set email alerts
|

CuI/Pd0 Cooperative Dual Catalysis: Tunable Stereoselective Construction of Tetra‐Substituted Alkenes

Abstract: This paper describes a tunable and stereoselective dual catalytic system that uses copper and palladium reagents. This cooperative silylcupration and palladium-catalyzed allylation readily affords trisubstituted alkenylsilanes. Fine-tuning the reaction conditions allows selective access to one stereoisomer over the other. This new methodology tolerates different substituents on both coupling partners with high levels of stereoselectivity. The one-pot reaction involving a Cu(I)/Pd(0) cooperative dual catalyst d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…A copper/palladium dual catalytic system was used by Riant and co-workers for the preparation of tetrasubstituted vinylsilanes by three-component coupling of acetylenic esters, allylic carbonates, and silylboranes in 2013 (252l -272l, Scheme 84). 105 By minor variation of the reaction conditions, E-and Z-configured coupling products were accessed in good yields with high stereoselectivity. There was no E/Z isomerization of coupling products when resubjected to the reaction (not shown).…”
Section: 2-addition To Het-het Double Bondsmentioning
confidence: 99%
“…A copper/palladium dual catalytic system was used by Riant and co-workers for the preparation of tetrasubstituted vinylsilanes by three-component coupling of acetylenic esters, allylic carbonates, and silylboranes in 2013 (252l -272l, Scheme 84). 105 By minor variation of the reaction conditions, E-and Z-configured coupling products were accessed in good yields with high stereoselectivity. There was no E/Z isomerization of coupling products when resubjected to the reaction (not shown).…”
Section: 2-addition To Het-het Double Bondsmentioning
confidence: 99%
“…The silylcupration of unsaturated substrates also provides a simple method for the generation of catalytically active silyl organocopper intermediates, which can be used in Pd‐catalyzed cross‐coupling. In 2014, the silylcopper(I) species were successfully employed in a Pd‐catalyzed allylic alkylation reaction by Riant and co‐workers (Scheme ) . Highly substituted and functionalized vinylsilanes can be prepared by Pd/Cu cooperative dual catalysis.…”
Section: Synergistic Cu‐si and Pd Catalysismentioning
confidence: 99%
“…The reaction of copper( i ) complexes with silyl boranes is known to give copper-silyl species, which Riant and co-workers showed will add across electron deficient alkynes to catalytically generate a vinyl-copper species to be used in palladium-catalysed cross-coupling ( Scheme 12 ). 47 In this instance allylic carbonates were used as the electrophiles. The authors found that the regioselectivity of the double bond could be controlled, switching between the Z - and E -isomers by omitting triphenylphosphine from the reaction conditions, and switching from simple copper chloride to NHC ligated IMesCu(DBM) (DBM = dibenzoylmethanate).…”
Section: Bimetallic Catalysis With Mononuclear Bond Breaking and Forminmentioning
confidence: 99%